VARIABILITY OF INDIAN SUMMER MONSOON : RELATIONSHIP WITH GLOBAL SST ANOMALIES (MAUSAM, 1994)
(iloh,tlcurr("!,1111111 ll111p .o; uflhe SlIllll1lt" r mUn!\4 lOn prt>cipil:lliull anomalies a nti St"a SU l f.IC(" Tt"mpt"1 a1lln"' (SST) a nUllul!it'.'i are pTt'St'IlI("d . n lir1 ) -)l' /u (1950..1479) rime St' 1; ("S uf 11l0n...nnn ind("x b co rn' l a h~d ....; Ih Iht"SST tillll' Sl'riCS al t"nch 1° ;I,:eans usi ng COADS (Comprehensive O..:eanAllno...pl1("fl." Dala S('1)dn ta ttl "3riOUS timc IJgs o f lUonth s (i.t' .. l1luI11 h,'S of year s p recedi ng 'lI1.1 conc urrcnI lu Ihe1ll011Stllll1-)l'at) , Ctl lTclal ion..mups :'I ll' pn.-pUTl,.f 111111 Illaly"I'" 1(1 i.lclltify Il' IN."Oll lle ct it ln "-' Ilf llln ll....oon pTt'I,:ipil